The prevention and improvement effects of vitamin D on type 2 diabetes mellitus: evidence from an umbrella review on Meta-analyses of cohort studies and randomized controlled trials - Cheng, Le; Lv, Chenhui; Xue, Lushan; Zhang, Cheng; Wang, Lili; Wang, Xi; Chen, Shuangzhi; Li, Xuemin; Feng, Wenjuan; Xie, Haoran; Zhao, Haifeng (Frontiers in Nutrition, 2024)
Background: To clarify whether Vitamin D prevent the occurrence of type 2 diabetes mellitus (T2DM) and improve glucose control in T2DM patients, we conducted this umbrella review, taking into account the inconsistent results of existing Meta-analyses. We aim to reveal the causal relationship between Vitamin D and T2DM through summarizing Meta-analyses of observational studies, and clarify the improvement on glucose control in T2DM patients through summarizing Meta-analyses of RCT studies between Vitamin D supplementation and T2DM patients, especially in T2DM patients with Vitamin D deficiency.We collected the Meta-analyses of observational studies and RCTs in PubMed, Scopus, Embase, Web of Science, and Cochrane.Results: 16 Meta-analyses (6 effect sizes for cohort studies and 10 effect sizes for RCTs) were included in the umbrella Meta-analyses. Random-effects model was carried out to calculate the pooled point estimates and their respective 95 % confidence intervals (CI). The results revealed that lower 25(OH)D levels increased the risk of T2DM (Pooled ESRR=1.34; 95%CI: 1.16, 1.53), Vitamin D supplementation ameliorated FBG (ES=-0.56; 95%CI: -1.00, -0.11), HbA1c (ES=-0.11; 95%CI: -0.20, -0.02), insulin (ES=-0.38; 95%CI: -0.59, -0.18) and HOMA-IR (ES=-0.37; 95%CI: -0.57, -0.16) in T2DM patients, especially in those with Vitamin D deficiency (FBG=-0.98; HbA1c=-0.27; HOMA-IR=-0.52).The present umbrella Meta-analyses demonstrates the potential benefits of higher serum Vitamin D levels and Vitamin D supplementation in reducing the development and symptoms of T2DM.